Toxoplasmosis impact on prematurity and low birth weight - Hurt, Karel; Kodym, Petr; Stejskal, David; Zikan, Michal; Mojhova, Martina; Rakovic, Jakub (PLoS One, 2022)
BACKGROUND: Toxoplasma gondii, one of the most common parasites, causes toxoplasmosis, one of the most frequent zoonotic diseases worldwide. T. gondii infects about one-third of the world's population. T. gondii infection is generally considered a major risk for spontaneous abortion, prematurity and low birth weight in the animal sphere. Less commonly, a toxoplasma serological profile is correlated with the particular data of delivery. Acute T. gondii infection during pregnancy often leads to spontaneous abortion and/or a severe injury of the eyes, brain, and other structures of the foetus. Latent T. gondii infection of pregnant women could lead to less obvious but important changes during pregnancy, including the end product of pregnancy and the timing of labour. This study aimed to contribute to the current knowledge by comparing serological T. gondii profiles of pregnant women with prematurity and low birth weights of newborns. MATERIAL AND METHODS: A retrospective study design was adopted. The study participants included a cohort of 1733 pregnant women who consecutively gave birth to their children and underwent regular antenatal biochemical screening between the 14th and 16th weeks of pregnancy. Prematurity was defined as the liveborn preterm delivery in gestational age of pregnancy <37 weeks. Low birth weight was defined as weight at birth of ≤2499 grams. The complement-fixation test (CFT) provided serological profiles for toxoplasmosis that expresses the overall levels of toxoplasma immunoglobulins of all classes. Enzyme-linked immunosorbent assay (ELISA) tests for IgG and IgM were used simultaneously. IgM positivity helped to differentiate acute from the latent stage of toxoplasmosis. Birth data, especially the week of delivery and fetal weight, were evaluated accordingly. RESULTS: Of the 1733 pregnant women, 25% were diagnosed as latent toxoplasma positive, and 75% as toxoplasma negative. There were 87 premature deliveries versus 1646 timely births. We observed 88 low birth weights and 1645 normal fetal weights. We found a statistically significant association between latent toxoplasmosis and prematurity, χ2(1) = 5.471, p = .019 and between latent toxoplasmosis and low birth weight of newborns, χ2(1) = 7.663, p = .006. There was a 1.707 times higher risk of prematurity for toxoplasma-positive women, while the risk for low birth weight was 1.861 times higher. The strength of both tests of association was mild. We tested the correlation between the levels of CFT titres and week of delivery and weight of newborns. No association was found between the level of latent toxoplasmosis and the week of delivery and fetal weight. CONCLUSION: Latent toxoplasmosis was associated with premature birth rate and lower birth weight of newborns. The odds of premature delivery was 1.7 and low birth weight 1.9 times higher in women with latent toxoplasmosis compared to toxoplasma negative women. Even though the strength of the association in our large sample is relatively mild, the combination of latent toxoplasmosis with other adverse factors could cause serious harm. Whole CFT and specific IgG levels of latent toxoplasmosis are not linked to the severity of prematurity or low birth weight in newborns.
Keywords: Premature Birth; dospělí; předčasný porod; Female; Infant; Prevalence; novorozenec; Toxoplasmosis; Adult; ženské pohlaví; Pregnant People; lidé; Infant, Newborn; parazitární komplikace těhotenství; Infant, Low Birth Weight; těhotenství; Toxoplasma; novorozenec s nízkou porodní hmotností; Risk Factors; prevalence; retrospektivní studie; séroepidemiologické studie; těhotné ženy; Infant, Premature, Diseases; kojenec; sérologické testy; Seroepidemiologic Studies; nemoci nedonošenců; rizikové faktory; nemoci novorozenců; toxoplazmóza; Serologic Tests; Pregnancy; Retrospective Studies; Infant, Newborn, Diseases; Pregnancy Complications, Parasitic; Humans